2013
DOI: 10.1002/jgrd.50062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the dynamic surface bareness on dust source function, emission, and distribution

Abstract: In this study we report the development of a time dependency of global dust source and its impact on dust simulation in the Goddard Chemistry Aerosol Radiation and Transport (GOCART) model. We determine the surface bareness using the 8 km normalized difference vegetation index (NDVI) observed from the advanced very high resolution radiometer satellite. The results are used to analyze the temporal variations of surface bareness in 22 global dust source regions. One half of these regions can be considered perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Such region‐specific, temporally varying erodibility can be specified by combining the land cover map and the monthly dynamic erodibility map presented in this study. This conclusion is also supported by some recent studies [e.g., Kim et al ., ] that observed improvements in dust emission using a MODIS NDVI (normalized difference vegetation index) based, dynamic dust source function.…”
Section: Discussion and Modeling Perspectivementioning
confidence: 99%
“…Such region‐specific, temporally varying erodibility can be specified by combining the land cover map and the monthly dynamic erodibility map presented in this study. This conclusion is also supported by some recent studies [e.g., Kim et al ., ] that observed improvements in dust emission using a MODIS NDVI (normalized difference vegetation index) based, dynamic dust source function.…”
Section: Discussion and Modeling Perspectivementioning
confidence: 99%
“…Both satellites and ground-based instruments can be used to measure 44 AOD in the atmosphere, but within the same temporal coordinates and geographic location 45 different instruments could generate different retrievals (Kahn et al, 2007, Kokhanovsky et 46 al., 2007, Liu et al, 2008and Mishchenko et al, 2009 Since the turn of the 21 st century, an upward trend of remotely sensed and ground-based 48 AOD and air pollutants was observed over the Middle East and North Africa (El-Askary 49 2009, Ansmann et al 2011, Yu et al 2013, Chin et al 2014, Yu et al 2015, Farahat et al 50 2016, Solomos et al 2017. This positive trend is attributed to the increase in the Middle 51 Eastern dust activity (Hsu et al, 2012) due to changes in wind speed and soil moisture 52 (Ginoux et al 2001 andKim et al 2013). Yu et al, (2015) concluded that the persistent La 53…”
Section: Introduction 28mentioning
confidence: 99%
“…Barren lands are one of the major sources of atmospheric dusts [2][3][4]. The dust aerosols affect the Earth's radiation budget by scattering and absorbing solar radiation and modifying the structure and properties of clouds [5][6][7].…”
Section: Introductionmentioning
confidence: 99%